Potential of Marine Fish Viscera–Derived Starter Microorganisms for Biogas Production Using a Mixed Biomass of Salvinia molesta and Corn Husk (Zea mays) - Suhirman Suhirman; Sela Kong (Fakultas Teknik Universitas Wahid Hasyim, 2026)
Cilegon City, Banten Province, Indonesia, generates abundant organic waste in the form of marine fish viscera (MFV) from fish-cleaning activities in traditional markets, which remains largely underutilized. This study aimed to evaluate the potential of MFV as an alternative bacterial starter for biogas production through the co-digestion of water hyacinth (KIM) and corn husk (KJ) biomass. Prior to digestion, KIM and KJ were physically pretreated to a particle size of 50–60 mesh, then chemically pretreated with 0.1 M NaOH. The pretreated biomass was then oven-dried at 60 °C for 24 h. Various KIM: KJ mass ratios were investigated, including 10:0, 8:2, 6:4, 4:6, 2:8, and 0:10, with a constant total solids (TS) content of 10 g. In addition, the biomass-to-MFV starter ratios were varied to 1:0.5, 1:1, 1:1.5, and 1:2. Anaerobic batch fermentation was conducted at an initial pH of 8, with 160 mL of distilled water added per 10 g TS. Methane content was analyzed using a Shimadzu GC-8A equipped with a thermal conductivity detector (TCD) at the National Research and Innovation Agency (BRIN), Indonesia. Biogas volume was measured at two-day intervals over a 50-day fermentation period. The results demonstrated that the optimum biomass composition was achieved at a KIM:KJ ratio of 4:6, yielding a biogas production of 65 mL g⁻¹ TS. The optimum biomass-to-starter ratio of 1:1 resulted in a total biogas volume of 986 mL, a biogas yield of 99 mL g⁻¹ TS, and an organic matter conversion efficiency of 65% after 50 days of fermentation, with methane content reaching 60% (v/v). This study introduces a novel approach by demonstrating, for the first time, the use of marine fish viscera as a bacterial starter in the co-digestion of KIM and KJ, highlighting its significant potential to enhance biogas yield while valorizing marine processing waste.